Democracy, Democracies and Democracy Discourses in Nepal: An Anthropologist’s Engagement - Dhakal, Suresh (Dhaulagiri Journal of Sociology and Anthropology, 2014)
Democracy is conceptualized and practiced differently in different times and places; and may exist in various forms and levels with various degrees and dimensions. Therefore the use of the word “democracy” occurs neither alone, nor steadily, nor completely; it is, “historically” and “ethnographically emergent”. Following an extensive review, the paper concludes that democracy (ideals, institutions and practices) is depended upon effective state vis-à-vis strong civil society. Effectiveness of the state and the strength of the civil society, both depend on a common denominator, that is, participation. This paper, excavates some of the traces of, what we may like to refer today as democracy, in our own historical context; and, portrays how the meaning of democracy shifting along with the shifting of the local terms for democracy. DOI: http://dx.doi.org/10.3126/dsaj.v7i0.10440 Dhaulagiri Journal of Sociology and Anthropology Vol. 7, 2013; 133-156